2019
DOI: 10.21203/rs.2.14707/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Husbands’ participation in birth preparedness and complication readiness and associated factors in Kucha district, GamoGofa Zone, Southern Ethiopia

Abstract: Background Birth-preparedness and complication-readiness (BPCR) is the process of planning for normal birth and anticipating the actions needed in case of an emergency. The involvement of husband during pregnancy and its complication helps an expectant mother to make timely decisions to avoid delays. Therefore, this study aims to assess the level of husband involvement in birth preparedness and complication readiness and associated factors in Kucha District, Gamo Zone, Southern Ethiopia.Methods Community-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The minimum birth preparedness and complication readiness among male partners of pregnant women and nursing mothers in the global south was 30% seen in a study conducted in Ethiopia [52] whereas the maximum was 57.6% observed in Nepal [42]. The pooled result of the studies showed that less than half (48.8%; 95%CI: 41.9, 55.6) of male partners of pregnant women and nursing mothers practiced BP/CR (Fig 2).…”
Section: Review Ndingsmentioning
confidence: 96%
See 3 more Smart Citations
“…The minimum birth preparedness and complication readiness among male partners of pregnant women and nursing mothers in the global south was 30% seen in a study conducted in Ethiopia [52] whereas the maximum was 57.6% observed in Nepal [42]. The pooled result of the studies showed that less than half (48.8%; 95%CI: 41.9, 55.6) of male partners of pregnant women and nursing mothers practiced BP/CR (Fig 2).…”
Section: Review Ndingsmentioning
confidence: 96%
“…The total sample size of the included studies in this review were 4210, ranging among studies included from 125 in Nepal [42] to 592 in Ethiopia [43]. Five of the included studies were from Asia [10,42,[44][45][46], seven studies from Africa with the majority from Ethiopia [43,[47][48][49][50][51][52]. Additionally, all studies included in the review were cross-sectional study designs (Table 1).…”
Section: Study Inclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current systematic review and meta-analysis, four regions and one administrative town in the country were included. Three studies were from Tigray [25][26][27], two were from Oromia region [28,29]. (Fig.3).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%